WAKAF PRODUKTIF DI INDONESIA - Muhammad Ismail; Noor Helmalia Agus; Erwan Setyanoor (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Productive waqf is one of the Islamic economic instruments with great potential to support social development and community economic empowerment. In Indonesia, waqf assets are widely distributed in various forms; however, most of them are still managed traditionally and not optimally. This study aims to describe the condition of productive waqf in Indonesia, identify the main challenges in its management, and formulate more effective and sustainable development approaches. This research employs a qualitative approach using a literature review method by analyzing scientific publications, waqf-related regulations, and previous research findings. The results indicate that the low professionalism of nazhir, limited public literacy regarding waqf, weak technical regulations, and lack of innovation in asset management are the main obstacles to the development of productive waqf. Therefore, transparent, professional, and empowerment-based waqf management is necessary to ensure that waqf can optimally contribute to social welfare and sustainable economic development.